Outcome of retinoblastoma treatment protocol in Cameroon as per SIOP‐PODC recommendation for a low‐income setting. Issue 8 (11th April 2022) - Kruger, Mariana; van Elsland, Sabine L.; Afungchwi, Glenn M.; Bardin, Richard; Njodzeka, Bernard; Kouya, Francine; Nfor, Patience; Nana, Philippa; Wharin, Paul; Hesseling, Peter B.
Abstract: Introduction: The International Society of Paediatric Oncology‐Paediatric Oncology in Developing Countries (SIOP‐PODC) group recommended graduated‐intensity retinoblastoma treatment for children in low‐ and middle‐income countries with limited local resources. Aim: The aim was to improve outcome of children with retinoblastoma by means of a treatment protocol for low‐income settings as recommended by the SIOP‐PODC recommendation in Cameroon. Methods: Children diagnosed with retinoblastoma between 2012 and 2016 were treated in two Baptist Mission hospitals in Cameroon, staging according to the International Retinoblastoma Staging System. Treatment included local therapy and combination chemotherapy (vincristine, cyclophosphamide, and doxorubicin) with or without surgery as per SIOP‐PODC guidelines for low‐income countries. Endpoint was survival at 24 months. Kaplan–Meier curves with log‐rank (Mantel–Cox) chi‐square ( χ 2 ) with respective p ‐values were prepared. Results: Eighty‐two children were included, of whom 79.3% had unilateral disease. The majority were males (61.0%) with median age 24 months (range 1–112 months; standard deviation [SD] 19). Limited disease was diagnosed in 58.5%, metastatic disease in 35.4%, and unknown stage in 6.1%. Overall survival (OS) was 50.0% at 24 months post diagnosis, but 68.8% for limited disease. Estimated cumulative survival at 24 months was 0.528 (standard error [SE] 0.056). Causes of death included disease progression/relapses (60.5%), neutropenic sepsis (15.9%), unknown causes (18.4%), unrelated infection (2.6%), and death post surgery (2.6%). Stage was significantly associated with OS ( p  < .001). Conclusion: Stage was the most significant factor for good OS and demonstrated the efficacy and feasibility of the SIOP‐PODC‐proposed management guidelines for retinoblastoma in a lower middle‐income setting.